2014
DOI: 10.1007/s11704-014-4177-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding taxi drivers’ routing choices from spatial and social traces

Abstract: Most of our learning comes from other people or from our own experience. For instance, when a taxi driver is seeking passengers on an unknown road in a large city, what should the driver do? Alternatives include cruising around the road or waiting for a time period at the roadside in the hopes of finding a passenger or just leaving for another road enroute to a destination he knows (e.g., hotel taxi rank)? This is an interesting problem that arises everyday in cities all over the world. There could be differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…The proposed approach provides a path for a taxi while optimizing a certain cost function, such as traveled distance or gasoline consumption. In [32], the authors found out that driver's cruising choice is learned from his/her previous experience and his/her interactions with other drivers. In [33], the authors proposed pCruise system to reduce the taxi's cruising miles by providing the shortest cruising route with at least one expected available passengers for this route.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed approach provides a path for a taxi while optimizing a certain cost function, such as traveled distance or gasoline consumption. In [32], the authors found out that driver's cruising choice is learned from his/her previous experience and his/her interactions with other drivers. In [33], the authors proposed pCruise system to reduce the taxi's cruising miles by providing the shortest cruising route with at least one expected available passengers for this route.…”
Section: Related Workmentioning
confidence: 99%
“…To address the problem that noisy expert behaviors degrade the IRL performance significantly, a robust IRL framework was developed in [16]. Liu et al [17]- [19] proposed a novel, non-density-based approach called mobility-based clustering to perceive the vehicle crowdedness in nearby areas by using their instant mobility, and then they proposed a Gaussian Process Dynamic Congestion Model for analyzing rationality from trajectories in terms of a set of impact factors. A novel approach based on matrix completion (MC) was proposed to recover the successive missing and corrupted data in [20].…”
Section: B Related Workmentioning
confidence: 99%
“…Pick-up locations usually represent the hot spots where there are high taxi travel demands [2,21,28,32]. Thus, we can unite the historical pick-up information to explore high-demand areas and analyze the distribution patterns of pick-up hot spots.…”
Section: Cluster Of Pick-up Locationsmentioning
confidence: 99%